Pre-K Program as Panacea to Academic Performance and Achievement Gaps between High and Low Socio-Economic Status (SES) Students in Nigeria (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
The fact that socio-economic status (SES) impacts on academic performance and achievement is universally established. Abundant researches have shown that students from high socio-economic background academically perform better than their peers from low socio-economic background. The fact is beyond contention. Interest and energy of educationists should be focused on solving the problem. Therefore, this paper prescribed the Pre-K Program as a veritable and effective solution to academic performance and achievement gaps existing between students due to SES of their parents. It is opined that the implementation of the Pre-K Program as recommended by this paper will eliminate the problem of existence of academic performance and achievement gaps between students of low and high SES background and parentage. The government of Nigeria and all stake holders in the educational sector are called upon to rise to the situation in eliminating the effects of SES on academic performance and achievement gap of students.